1995
DOI: 10.3354/dao020191
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical properties and drug resistance of Aeromonas salmonicida in Finland

Abstract: The biochemical properties of 105 Aeromonas salmonicida (AS) strains were examined in order to find criteria for distinguishing between 'typicals' and 'atypicals' and for further subdividing the 'atypicals'. One hundred of the strains had been isolated from fish at 35 fish farms and 5 from wild fish between 1986 and 1991. The fishes involved were as follows: lamprey, whitefish, rainbow trout. salmon, sea trout, brown trout, arctic char, lake trout, grayling, dace and roach. Typical (AS subsp. salmonicida) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 9 publications
(17 reference statements)
1
7
0
Order By: Relevance
“…Although Dalsgaard et al. (1998) and Austin & Austin (2007) reported that the majority of atypical A. salmonicida do not degrade aesculin, in our study, all isolates hydrolysed aesculin after 48 h, as also reported by other authors (Dalsgaard & Paulsen 1986; Hirvelä‐Koski, Koski & Niiranen 1994). In addition, our isolates showed divergences from the reference strains in amino acid utilization.…”
Section: Discussionsupporting
confidence: 88%
“…Although Dalsgaard et al. (1998) and Austin & Austin (2007) reported that the majority of atypical A. salmonicida do not degrade aesculin, in our study, all isolates hydrolysed aesculin after 48 h, as also reported by other authors (Dalsgaard & Paulsen 1986; Hirvelä‐Koski, Koski & Niiranen 1994). In addition, our isolates showed divergences from the reference strains in amino acid utilization.…”
Section: Discussionsupporting
confidence: 88%
“…The Finnish AAS isolates from these fish species differ from the well‐characterized AAS causing disease in Atlantic salmon, Salmo salar L., in Iceland (Gudmundsdóttir 1997; Gudmundsdóttir, Hvanndal, Björnsdottir & Wagner 2003). The AAS isolates, phenotypically similar to isolates from Arctic charr and European grayling, have also been obtained from several other fish species in Finland (Hirvelä‐Koski, Koski & Niiranen 1994; Hänninen & Hirvelä‐Koski 1997, 1999).…”
Section: Introductionmentioning
confidence: 84%
“…The development of resistance to antibiotics among atypical strains has been observed by Hirvela-Koski et al (1994). who found resistance to sulfonamides.…”
Section: Controlmentioning
confidence: 94%
“…Wiklund et al (1992) bMcCarthy (1978, Bohm et al (1986). Olivier (1992) CAustin et al (1989) dPedersen et al (1994, Wiklund et al (1994), Wiklund & Dalsgaard (1995 'Dalsgaard & Fdulsen (1986), Hirvela-Koski et al (1994), Nakatsugatva (1994) McCarthy (1978), Bohm et al (1986) and Olivier (1992) classified the examined atypical strains as subspecies achromogenes and nova. Some important characteristics of these isolates were the same for all strains (Table 2), but subspecies nova seemed to be more fastidious and growth could require up to 5 d incubation at 22'C.…”
Section: Identification and Characterizationmentioning
confidence: 99%